Follicular keratosis of the face in pediatric patients of color. Issue 2 (17th February 2022) - Grullon, Karina; Ashi, Shaymaa A.; Shea, Christopher R.; Ruiz de Luzuriaga, Arlene M.; Stein, Sarah L.; Rosenblatt, Adena E.
Abstract: Background/Objectives: Follicular keratosis (FK) is a poorly understood disorder presenting with multiple, grouped hyperkeratotic follicular papules typically affecting the chin or jawline. This study describes the clinical presentation, histopathology, management, and outcomes of a series of pediatric patients of color with FK of the face, thought to be related to rubbing or friction on the skin. Methods: Retrospective review of 20 pediatric patients with FK of the face who presented to our pediatric dermatology practice between April 2019 and October 2021. Results: Twenty patients (mean age 12.1 years, 13 females), all self‐identified as Black/African American, were included. All presented with an initially asymptomatic, hyperpigmented patch containing multiple hyperkeratotic follicular papules, located on the cheek, chin, upper lip, and/or jawline. Five patients endorsed a history of rubbing the site. Nine patients had onset of the lesions during the COVID‐19 pandemic. Treatments included topical vitamin D analogs, corticosteroids, and/or retinoids. Topical vitamin D analogs and retinoids improved the texture and hyperpigmentation of the follicular lesions in only four patients, while topical corticosteroids had no effect. Histopathological examination of two patients revealed multiple dilated follicles containing keratinized material and associated with a sparse dermal inflammatory infiltrate in one patient and granulomatous inflammation within the dermis in the other. Conclusions: In our cohort of pediatric patients with FK, patients of color were preferentially affected, and all cases were associated with hyperpigmentation. Some patients presented during the COVID‐19 pandemic suggesting that friction from facial mask wearing may have induced or exacerbated this uncommon condition.